Study Of Impulse Buying Behavior On Interest In Using Paylater Facilities In The Marketplace With Celebrity Endorsers As Mediations - Zahra, Zahra; Suleman, Dede; Wuryanto, Anus; Styaningrum, Etik Dwi; Rini, Ratih Setyo; Suhendra, Asep Dony; Supriatin, Supriatin; Setiawan, Adi Chandra (IJOSMAS, 2022)
The purpose of this study was to examine the effect of impulsive buying behavior on interest in using a paylater with celebrity endorser as an intervening variable. The sample of this study was 100 students in Jakarta who were selected using the convenience sampling method, data were collected using a questionnaire. The collected data is processed using SmartPls 3.0. The results of this study indicate that impulsive buying behavior has a significant effect on interest in using paylater. Celebrity endorser has no significant effect on interest in using paylater, Celebrity endorser also has no significant effect as an intervening variable